2009
DOI: 10.2193/2008-294
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Global Positioning System Telemetry Techniques for Estimating Cougar Predation Parameters

Abstract: Using clusters of locations obtained from Global Positioning System (GPS) telemetry collars to identify predation events may allow more efficient estimation of behavioral predation parameters for the study and management of large carnivore predator‐prey systems. Applications of field‐ and model‐based GPS telemetry cluster techniques, however, have met with mixed success. To further evaluate and refine these techniques for cougars (Puma concolor), we used data from visits to 1,735 GPS telemetry clusters, 637 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

13
281
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(298 citation statements)
references
References 32 publications
13
281
0
Order By: Relevance
“…Capturing and fitting carnivores with Global Positioning System (GPS) radio-transmitters allows for frequent relocations, which can facilitate location of kill sites (Knopff et al 2009), den locations , day beds (Anderson & Lindzey 2003) and rendezvous sites (Merrill & Mech 2003). Recently, several studies have used GPS technology to better understand prey selection and investigate kill sites of carnivores (Anderson & Lindsey 2003, Cavalcanti & Gese 2010, Ruth et al 2010).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Capturing and fitting carnivores with Global Positioning System (GPS) radio-transmitters allows for frequent relocations, which can facilitate location of kill sites (Knopff et al 2009), den locations , day beds (Anderson & Lindzey 2003) and rendezvous sites (Merrill & Mech 2003). Recently, several studies have used GPS technology to better understand prey selection and investigate kill sites of carnivores (Anderson & Lindsey 2003, Cavalcanti & Gese 2010, Ruth et al 2010).…”
mentioning
confidence: 99%
“…Recently, several studies have used GPS technology to better understand prey selection and investigate kill sites of carnivores (Anderson & Lindsey 2003, Cavalcanti & Gese 2010, Ruth et al 2010). This technology has been used to document kills by large carnivores including jaguars Panthera onca (Cavalcanti & Gese 2010), cougars Puma concolor (Anderson & Lindsey 2003, Knopff et al 2009) African lions Panthera leo (Tambling et al 2010), leopards Panthera pardus (Martin et al 2011) and gray wolves Canis lupus (Sand et al 2005, Demma et al 2007, Zimmerman et al 2007). However, we are unaware of any study assessing the effectiveness of this technique on medium-sized carnivores.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Even with the advent of Global Positioning Systems (GPS) radiocollars and cluster techniques to locate kill sites (Anderson and Lindzey 2003;Knopff et al 2009), Cougar scavenging events and rates are difficult to quantify. Previous studies (Bauer et al 2005) have shown that Cougars will treat scavenged carcasses similar to their own kills, and will cache and cover them with vegetation and soil.…”
mentioning
confidence: 99%